PEMBUATAN ALAT PENANGKAP SAMPAH PADA SALURAN DRAINASE UNTUK LINGKUNGAN YANG BERSIH DAN SOSIALISASI KEPADA WARGA DI JALAN BUNGA WIJAYA KESUMA, KOTA MEDAN - Parulian, Sopar; PSD, Almerinda Regina; L, Morin Morissa; Marshando, Panji; Sinurat, Meinarty (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Community Services at Jalan Bunga Wijaya Kesuma, Medan City is done to solve the problems faced by the community, namely the problem of waterlogging due to clogged drainage channels, caused by the accumulation of plastic waste and organic waste such as leaves. The activity that team carried out is the manufacture of an economical reuseable steel waste of trash rack a solution to this problem. The model and the dimension of the trash rack is designed first, then installed in the channel. The community services team did survey the reuseable steel waste, fabricated it, transported it to the location, and installed it in the drainage channel as a new trash rack. The location of the installation is coordinated with the Neighbourhood Head and the residents, there are two installation points. After that, socialization was also carried out to the community for regular maintenance of the trash rack to prevent garbage from garbage accumulating again.